2008
DOI: 10.1017/s0025315408001379
|View full text |Cite
|
Sign up to set email alerts
|

Diet composition and food habits of Caranx rhonchus (Carangidae) from the Gulf of Gabes (central Mediterranean)

Abstract: Caranx rhonchus (Carangidae) ranging from 6.5 to 30.6 cm in total length (TL), fished in the Gulf of Gabes (south Tunisia, central Mediterranean), were used to investigate feeding habits of the species. This study was based mainly on the evolution of the index of relative importance (IRI) with respect to sex, fish size and season. Among 1040 stomachs examined, 595 were empty (%VI ¼ 57.2). The vacuity index (%VI) differed significantly across months and declined slightly with season. A total of 13 species repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
(9 reference statements)
2
4
0
3
Order By: Relevance
“…The piscivorous nature of both species was verified in this study, as previously shown in other parts of the world (e.g. C. rhonchus: SLEY et al, (2007SLEY et al, ( , 2008; P. saltatrix: JUANES et al, (1993);DHIEB et al,(2001)). However, in order to determine their feeding preferences, potential diet overlap and competition for food resources in the area properly, a larger sample size of both species needs to be examined and a finer grouping of prey items is required.…”
Section: Discussionsupporting
confidence: 90%
“…The piscivorous nature of both species was verified in this study, as previously shown in other parts of the world (e.g. C. rhonchus: SLEY et al, (2007SLEY et al, ( , 2008; P. saltatrix: JUANES et al, (1993);DHIEB et al,(2001)). However, in order to determine their feeding preferences, potential diet overlap and competition for food resources in the area properly, a larger sample size of both species needs to be examined and a finer grouping of prey items is required.…”
Section: Discussionsupporting
confidence: 90%
“…Comparable studies about the food habits of other members of the family Carangidae have been carried out in the same region. The results from the present study suggest that the diet of C. crysos most closely resembles that of false scad, Caranx rhonchus (Sley et al , 2008), with both species feeding primarily on teleosts. However, studies on the diets of horse mackerel, Trachurus trachurus from the Tunisian coasts (Fezzani, 2006) and in the central Adriatic Sea (Santic et al , 2004), and pilotfish, Naucrates ductor in Sicilian waters indicated that these species fed mainly on zooplanktonic crustaceans, whilst teleosts were of minor importance.…”
Section: Discussionsupporting
confidence: 54%
“…Los resultados de este trabajo indican que, en la bahía de Acapulco, Guerrero C. vinctus se alimenta de una gran variedad de presas zooplanctónicas, representadas por crustáceos y huevos y larvas de peces, así como pequeños peces de la familia Engraulidae. Otras especies de la familia Carangidae que también basan su alimentación en crustáceos y peces se han considerado como depredadores especialistas (Roux & Conand, 2000;Sley, Jarboui, Ghorbel, & Bouain, 2008;Flores-Ortega et al, 2010;Sánchez-García et al 2017).…”
Section: Discussionunclassified
“…ISSN Impreso: 0034-7744 ISSN electrónico: 2215-2075 principalmente con redes de enmalle, línea de mano y con arpón (Smith-Vaniz, 1995;Espino-Barr, Cruz, & García, 2003;Gutiérrez-Zavala & Cabrera-Mancilla, 2019). Las especies pertenecientes al género Caranx son consideradas como depredadores piscívoros, sin embargo, también pueden alimentarse de crustáceos y en menor medida de moluscos y otros invertebrados (Silvano, 2001;Sley, Jarboui, Ghorbel, & Bouain, 2008;Saucedo-Lozano et al 2012). En algunas especies se ha determinado que la dieta durante la etapa juvenil se basa en el consumo de crustáceos y durante el crecimiento aumenta el consumo de peces hasta la fase adulta (Sley, Jarboui, Ghorbel, & Bouain, 2009).…”
unclassified